2017
DOI: 10.5194/amt-10-869-2017
|View full text |Cite
|
Sign up to set email alerts
|

Flux calculation of short turbulent events – comparison of three methods

Abstract: Abstract. The eddy covariance method is commonly used to calculate vertical turbulent exchange fluxes between ecosystems and the atmosphere. Besides other assumptions, it requires steady-state flow conditions. If this requirement is not fulfilled over the averaging interval of, for example, 30 min, the fluxes might be miscalculated. Here two further calculation methods, conditional sampling and wavelet analysis, which do not need the steady-state assumption, were implemented and compared to eddy covariance. Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 42 publications
8
72
0
Order By: Relevance
“…This similarity of result is consistent with observations from Schaller et al (2017). The real-valued Mexican hat wavelet , based on the second derivative of the Gaussian probability function, was chosen here to estimate the momentum and dust fluxes over nonstationary small time periods as such wavelet leads to a good resolution in time.…”
Section: Wavelet Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…This similarity of result is consistent with observations from Schaller et al (2017). The real-valued Mexican hat wavelet , based on the second derivative of the Gaussian probability function, was chosen here to estimate the momentum and dust fluxes over nonstationary small time periods as such wavelet leads to a good resolution in time.…”
Section: Wavelet Methodssupporting
confidence: 78%
“…Recently, Schaller et al (2017) demonstrated the performance of the wavelet technique compared to the EC one at estimating the flux of methane during nocturnal short turbulent events. Our analysis is based on the guide and wavelet tools proposed by Torrence and Compo (1998) in line with the analysis of Schaller et al (2017). Our analysis is based on the guide and wavelet tools proposed by Torrence and Compo (1998) in line with the analysis of Schaller et al (2017).…”
Section: Wavelet Methodsmentioning
confidence: 99%
“…The Morlet wavelet is the standard choice for eddy covariance calculations, giving reasonable localization in both time and frequency domains (Schaller et al, 2017). The CWT is well suited for airborne fluxes, offering several advantages over traditional EA and FFT.…”
Section: Continuous Wavelet Transform Fluxmentioning
confidence: 99%
“…Because highly non-steady state conditions were expected for CH 4 fluxes at this observation site, which pose a serious violation of the basic assumptions linked to the eddy-covariance method (Foken and Wichura, 1996), we applied a waveletbased calculation method as a second flux processing approach in addition to the standard eddy-covariance data processing. 20 Schaller et al (2017b) have developed a method for wavelet-based flux computation that offers the possibility of determining exact fluxes with a user-defined time resolution that can be as low as about 1 minute. Within the context of this study, we applied their calculation tool with a continuous wavelet transform using the Mexican hat wavelet (WV M h ), which provides an excellent resolution in the time domain.…”
Section: Raw Data Processing and Flux Calculationmentioning
confidence: 99%
“…The focus of the present study is on the interpretation of CH 4 emission events detected by a wavelet software package (Schaller et al, 2017b, a), which has already successfully been applied to the non-steady state fluxes during a solar eclipse 15 . This approach, which builds on the raw data sampled by EC towers, allows us to resolve fluxes not only over 30 minute averaging periods, but also for an averaging interval of 1 minute.…”
mentioning
confidence: 99%